2022
DOI: 10.1186/s13287-022-02818-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of pacing function by HCN4 overexpression in human pluripotent stem cell-derived cardiomyocytes

Abstract: Background The number of patients with bradyarrhythmia and the number of patients with cardiac pacemakers are increasing with the aging population and the increase in the number of patients with heart diseases. Some patients in whom a cardiac pacemaker has been implanted experience problems such as pacemaker infection and inconvenience due to electromagnetic interference. We have reported that overexpression of HCN channels producing a pacemaker current in mouse embryonic stem cell-derived card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
2
2
0
Order By: Relevance
“…Immunofluorescence staining of iPS-CMs results showed that cTnT-positive cells (red) and HCN4-positive cells (green) were observed in both groups, and they were high expressed in the stretch group compared with the control group. HCN4 channels are required for normal rhythm generation and conduction, playing a key role in cardiac pacing 21 , and HCN4 overexpression shows enhanced I(F) current, spontaneous discharge, and pacing in iPS-CMs 22 , which is consistent with our finding of increased cardiomyocytes contractility in the stretch group (Figure 5B). Experiments also confirmed the existence of sarcomere structure in the stretch group, these results indicating the maturation of myocardial tissue.…”
Section: Discussionsupporting
confidence: 90%
“…Immunofluorescence staining of iPS-CMs results showed that cTnT-positive cells (red) and HCN4-positive cells (green) were observed in both groups, and they were high expressed in the stretch group compared with the control group. HCN4 channels are required for normal rhythm generation and conduction, playing a key role in cardiac pacing 21 , and HCN4 overexpression shows enhanced I(F) current, spontaneous discharge, and pacing in iPS-CMs 22 , which is consistent with our finding of increased cardiomyocytes contractility in the stretch group (Figure 5B). Experiments also confirmed the existence of sarcomere structure in the stretch group, these results indicating the maturation of myocardial tissue.…”
Section: Discussionsupporting
confidence: 90%
“…During induced conversion, most cells adopt the spindle shape. HCN2 expression was able to induce the ASC conversion in culture, similar to previously tested HCN2 expression in MSCs following transplantation to the sites of SAN damage [17,20] or in cultured cardiac-like cells [24,25,33,37]. SHOX2 alone was not efficient in converting ASCs into differentiating cells [23,26].…”
Section: Unmodified Adrcs Containing Multipotent Ascs May Be Used As ...supporting
confidence: 76%
“…Previously, TBX5 was part of the recipes used for cell transdifferentiation into cardiomyocytes [45][46][47] and it likely stimulated NKX2.5 expression. In the case of ASCs, TBX5 expression potentially contributes to their cardiac differentiation making them somewhat closer to NKX2.5-expressing cardiac and cardiac-like cells used by other researchers [21,24,25,29,35,37,38,[41][42][43][44]. Furthermore, TBX5, which positively regulates the levels of SHOX2 and TBX3 in the developing may induce the expression of these pacemaker lineage genes during ASC conversion.…”
Section: Unmodified Adrcs Containing Multipotent Ascs May Be Used As ...mentioning
confidence: 95%
“…“pAAVS1_SA_loxP_PGK_ Neo _loxP/CAG_IRES_ EGFP/AmpR ” that we previously generated was used for a donor vector ( 15 ). Human SLC5A5 open reading frame (ORF) subcloned into pCMV6-XL5 vector (Cat.#.…”
Section: Methodsmentioning
confidence: 99%